Disruptive coloration provides camouflage independent of background matching - Schaefer, H. Martin; Stobbe, Nina (Proceedings of the Royal Society. B, Biological sciences, 2006)
Natural selection shapes the evolution of anti-predator defences, such as camouflage. It is currently contentious whether crypsis and disruptive coloration are alternative mechanisms of camouflage or whether they are interrelated anti-predator defences. Disruptively coloured prey is characterized by highly contrasting patterns to conceal the body shape, whereas cryptic prey minimizes the contrasts to background. Determining bird predation of artificial moths, we found that moths which were dissimilar from the background but sported disruptive patterns on the edge of their wings survived better in heterogeneous habitats than did moths with the same patterns inside of the wings and better than cryptic moths. Despite lower contrasts to background, crypsis did not provide fitness benefits over disruptive coloration on the body outline. We conclude that disruptive coloration on the edge camouflages its bearer independent of background matching. We suggest that this result is explainable because disruptive coloration is effective by exploiting predators' cognitive mechanisms of prey recognition and not their sensory mechanisms of signal detection. Relative to disruptive patterns on the body outline, disruptive markings on the body interior are less effective. Camouflage owing to disruptive coloration on the body interior is background-specific and is as effective as crypsis in heterogeneous habitats. Hence, we hypothesize that two proximate mechanisms explain the diversity of visual anti-predator defences. First, disruptive coloration on the body outline provides camouflage independent of the background. Second, background matching and disruptive coloration on the body interior provide camouflage, but their protection is background-specific.